Pre-Clinical Assessment of the Nose-to-Brain Delivery of Zonisamide After Intranasal Administration - Gonçalves, Joana (2020)
Zonisamide clinical indications are expanding beyond the classic treatment of epileptic seizures to Parkinson's disease and other neurodegenerative diseases. However, the systemic safety profile of zonisamide may compromise its use as a first-line drug in any clinical condition. Since zonisamide is marketed as oral formulations, the present study aimed at exploring the potential of the intranasal route to centrally administer zonisamide, evaluating the systemic bioavailability of zonisamide and comparing its brain, lung and kidney pharmacokinetics after intranasal, oral and intravenous administrations.